Magnetic powder core and preparation method thereof
By doping aluminum elements in iron-nickel alloys and increasing nickel content, combined with specific heat treatment and mechanical stress, an iron-nickel aluminum magnetic powder core with negative temperature loss characteristics was prepared, which solved the significant increase in the loss of the existing iron-nickel magnetic powder core at high temperatures. The problem of high results enables low loss performance and high magnetic permeability under high temperature conditions.
Patent Information
- Application Number
- CN202411723552.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
AI Technical Summary
The loss of existing iron-nickel magnetic powder cores increases significantly in high temperature environments, limiting their application range.
Iron-nickel aluminum alloy soft magnetic powder is used to prepare magnetic powder cores with negative temperature loss characteristics by doping aluminum elements and increasing nickel content, combining specific heat treatment processes and mechanical stresses, adjusting magnetic properties and temperature coefficients.
It realizes the low loss performance of the magnetic powder core under high temperature conditions, while maintaining high magnetic permeability and DC superposition performance, with a tight structure, high strength and strong corrosion resistance.
Smart Images

Figure BDA0005158658690000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic powder cores, and in particular relates to a magnetic powder core and a preparation method thereof. Background Art
[0002] Iron-nickel magnetic powder core is a metal powder magnetic core made of alloy powder of Fe and Ni. This magnetic powder core has stable working performance under high power, high DC bias or high frequency AC, and has been widely used in switching regulation inductors, online noise filters, flyback transformers, power factor correction and pulse transformers.
[0003] The loss characteristics of conventional iron-nickel magnetic powder cores show a positive temperature coefficient, that is, as the operating temperature increases, the loss characteristics of the material will significantly increase and deteriorate, greatly limiting its application in high-temperature environments. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of the magnetic powder core in the prior art that the loss is significantly increased under high temperature conditions, thereby providing a magnetic powder core and a preparation method thereof.
[0005] To this end, the present invention provides the following technical solutions.
[0006] In a first aspect, the present invention provides a method for preparing a magnetic powder core, comprising the following steps:
[0007] S1. preparing magnetic powder;
[0008] The magnetic powder is an iron-nickel-aluminum alloy soft magnetic powder, wherein the mass percentage of iron is 37% to 42%, the mass percentage of nickel is 60% to 64%, and the mass percentage of aluminum is 2.5% to 3%;
[0009] S2, heat treating the magnetic powder under pressure;
[0010] S3, coating the product of S2;
[0011] S4, pressing the product of S3 into a blank;
[0012] S5. Heat-treating the blank to obtain a magnetic powder core.
[0013] In a possible implementation manner, the S2 includes:
[0014] S201, mixing magnetic powder with nano-mica powder and chromium trioxide;
[0015] S202, heat treating the product of S201 under pressure;
[0016] In a possible implementation manner, the nano-mica powder accounts for 0.1% to 0.2% of the mass of the magnetic powder;
[0017] In a possible implementation manner, the chromium trioxide is 0.05% to 0.1% of the mass of the magnetic powder;
[0018] In a possible implementation, S201 includes: first mixing magnetic powder with nano-mica powder to obtain a mixture, dissolving chromium trioxide in a first solvent to obtain a first solution, and then mixing the mixture with the first solution and drying;
[0019] Preferably, the first solvent comprises one or more of acetone and water;
[0020] Preferably, the first solvent accounts for 5% to 10% of the mass of the magnetic powder.
[0021] In a possible implementation manner, the pressure in S2 is 5 kPa to 10 kPa.
[0022] In one possible implementation, the heat treatment in S2 includes:
[0023] Heat up from room temperature to 340℃~380℃ at the first heating rate, and keep warm for 0.5~1h; continue to heat up to 740℃~750℃ at the second heating rate, and keep warm for 1~3h; cool down to 620℃~640℃ at the first cooling rate, and keep warm for more than 2h; cool down to 460~500℃ at the second cooling rate, and then cool down to room temperature with the furnace;
[0024] Preferably, the first heating rate is 10-15°C / min;
[0025] Preferably, the second heating rate is 5 to 8°C / min;
[0026] Preferably, the first cooling rate is 1-2°C / min;
[0027] Preferably, the first cooling rate is 0.5-1°C / min;
[0028] Preferably, the hydrogen atmosphere is maintained throughout the heat treatment;
[0029] Preferably, the furnace pressure of the heat treatment is controlled at 0.2-0.3 MPa.
[0030] In a possible implementation, S1 includes: mixing iron, nickel, and aluminum according to a mass ratio, melting, and atomizing to obtain an iron-nickel-aluminum alloy soft magnetic powder;
[0031] Preferably, the melting temperature is 1500-1800°C and the melting time is 2-3h;
[0032] Preferably, the melting is carried out under vacuum conditions;
[0033] Preferably, the atomization is a high-pressure gas-water combined atomization method, and more preferably, the gas pressure of the high-pressure gas-water is 1 to 6 MPa;
[0034] Preferably, S1 further comprises sieving to obtain magnetic powder with a particle size of 16 μm-34 μm.
[0035] In a possible implementation, S3 includes:
[0036] S301, mixing the product of S2 with a silane coupling agent;
[0037] S302, mixing the product of S301 with silicone resin;
[0038] Preferably, the silane coupling agent includes one or more of acrylic silane coupling agent, KH560 and KH570; more preferably, the silane coupling agent is A-189 silane coupling agent;
[0039] Preferably, the silicone resin includes one or more of polydimethylsiloxane, methylphenyl silicone resin and methyl silicone resin;
[0040] Preferably, the amount of the silane coupling agent is 0.5% to 0.6% of the mass of the magnetic powder;
[0041] Preferably, the amount of silicone resin used is 0.8% to 1% of the mass of the magnetic powder.
[0042] In a possible implementation, S301 includes first dissolving the silane coupling agent in a second solvent to obtain a second solution, and then mixing the product of S2 with the second solution and drying;
[0043] In one possible embodiment, the second solvent includes one or more of acetone and water;
[0044] In a possible implementation manner, the second solvent is 5% to 10% of the mass of the magnetic powder;
[0045] In a possible implementation, S302 includes first mixing the silicone resin with a third solvent to obtain a third solution, and then mixing the product of S301 with the third solution and drying;
[0046] In one possible embodiment, the third solvent includes one or more of acetone and water;
[0047] In a possible implementation manner, the third solvent accounts for 5% to 10% of the mass of the magnetic powder.
[0048] In one possible embodiment, S4 comprises the product of S3 mixed with a release agent and then pressed into shape;
[0049] In a possible implementation, the release agent includes zinc stearate and / or aluminum stearate;
[0050] In a possible implementation manner, the amount of the release agent is 0.3%-0.4% of the mass of the magnetic powder;
[0051] In a possible implementation manner, the pressure of the pressing molding is 1800-2000 MPa.
[0052] In a possible implementation, S5 includes keeping the blank at 700-750° C. for 1-2 hours in a nitrogen atmosphere to obtain a magnetic powder core.
[0053] In a second aspect, the present invention provides a magnetic powder core manufactured according to the method.
[0054] S5 heat treats the blank to treat the coated material and remove the internal stress generated during the pressing process.
[0055] In the iron-nickel-aluminum alloy soft magnetic powder, the sum of the mass percentages of iron, nickel and aluminum is 100%.
[0056] In a possible implementation, in S201, after the mixture is mixed with the first solution, it is placed in a mixer and stirred at room temperature for 30-50 minutes, and then evenly spread out and placed in a vacuum oven at 120° C. for drying for 1-1.5 hours.
[0057] The technical solution of the present invention has the following advantages:
[0058] 1. The preparation method of the magnetic powder core of the present invention comprises the following steps: S1, preparing magnetic powder; the magnetic powder is an iron-nickel-aluminum alloy soft magnetic powder, wherein the mass percentage of iron is 37% to 42%, the mass percentage of nickel is 60% to 64%, and the mass percentage of aluminum is 2.5% to 3%; S2, heat treating the magnetic powder under pressure; S3, coating the product of S2; S4, pressing the product of S3 to obtain a blank; S5, heat treating the blank to obtain a magnetic powder core.
[0059] The present invention increases the insulation of the alloy powder to reduce its loss by doping aluminum elements in the iron-nickel alloy. By increasing the nickel content in the iron-nickel alloy and doping with aluminum elements, the growth of grains is inhibited, the diffusion of grain boundaries is slowed down, the grain boundary structure of the alloy is improved, and the thermal stability of the material is improved. At the same time, the crystal structure of the material and the growth direction of the magnetic domain wall are directionally controlled by a specific heat treatment method under the action of mechanical stress, thereby adjusting the magnetic properties and temperature coefficient, and promoting the magnetic powder core to produce loss negative temperature characteristics, so as to achieve excellent low-loss performance of the magnetic powder core under high temperature conditions. The magnetic powder core prepared by the present invention also maintains a relatively high magnetic permeability and DC superposition performance, and the magnetic powder core has a compact structure, high strength, and strong corrosion resistance.
[0060] The magnetic powder core provided by the present invention has a negative loss temperature coefficient within a certain range (within 125° C.), and the temperature characteristics of its magnetic properties can be controlled by adjusting the element ratio and the heat treatment process, thereby solving the problem of deterioration of loss performance of conventional iron-nickel magnetic powder cores at high temperatures. DETAILED DESCRIPTION
[0061] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0062] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.
[0063] Example 1
[0064] This embodiment provides a method for preparing a magnetic powder core, comprising the following steps:
[0065] S1. Preparation of magnetic powder:
[0066] S101. Mix iron, nickel and aluminum in a mass percentage of 39:58.5:2.5.
[0067] S102. After mixing, it was added to an atomizing furnace and heated at 1600°C for 2 hours to melt. The iron-nickel-aluminum alloy soft magnetic powder was prepared by atomization of high-pressure gas-water combined atomization method, and the gas pressure of the high-pressure gas-water was 3Mpa;
[0068] S103. Sieve the above-mentioned iron-nickel-aluminum alloy soft magnetic powder to obtain magnetic powder with a particle size of 16μm-34μm.
[0069] S2. Heat treatment:
[0070] S201. Evenly mix the magnetic powder obtained in S1 with nano-mica powder accounting for 0.1% of the mass of the magnetic powder, dissolve chromium trioxide accounting for 0.05% of the mass of the magnetic powder in acetone, and then evenly mix the two, place in a blender and stir at room temperature for 30 minutes, then spread evenly and place in a vacuum oven at 120°C for drying for 1 hour. The amount of acetone used is 10% of the mass of the magnetic powder.
[0071] S202. The product of S201 is taken out and passed through a 200-mesh sieve. The material under the sieve is placed in a pressurizing device, and mechanical pressure is applied in the horizontal front and back, left and right, and vertical directions to make its surface withstand a pressure of 5 kPa. On the basis of the presence of mechanical stress, the iron box is placed in a sintering furnace for annealing, and the temperature is increased from room temperature to 340°C at a heating rate of 15°C / min, and kept warm for 0.5h, then increased to 750°C at a heating rate of 5°C / min, and kept warm for 1h, and then decreased to 620°C at a cooling rate of 1°C / min, and kept warm for more than 2h; then decreased to 480°C at a cooling rate of 0.5°C / min, and then cooled to room temperature with the furnace, and maintained in a hydrogen atmosphere throughout the process, and the furnace pressure was controlled at 0.2-0.3Mpa.
[0072] S3, coating the product of S2:
[0073] S301, after passing the product of S2 through a 200-mesh sieve, mix the sieve material with an acetone solution containing A-189 silane coupling agent (containing more than 98% isopropyl acrylate silane) and dry it in an oven at 60° C. The A-189 silane coupling agent is 0.5% of the mass of the magnetic powder, and the acetone is 10% of the mass of the magnetic powder.
[0074] S302, the product of S301 is passed through a 200 mesh sieve, the sieve material is mixed evenly with an acetone solution containing polydimethylsiloxane (Shanghai Dingfen Chemical Technology Co., Ltd., molecular weight 9000-14000), and air-dried at room temperature, and then passed through an 80 mesh sieve after drying. The polydimethylsiloxane is 0.8% of the mass of the magnetic powder, and the acetone is 10% of the mass of the magnetic powder.
[0075] S4, pressing and molding:
[0076] The product of S3 was mixed with a mold release agent and pressed with a servo press, with the inner and outer diameters of the mold being: ID = 9.7 mm, OD = 12.7 mm. The pressure was 2000 MPa, and the corresponding magnetic ring blank was obtained. The mold release agent was zinc stearate, and the amount used was 0.3% of the mass of the magnetic powder.
[0077] S5: placing the magnetic ring blank in a nitrogen atmosphere at 700°C for 1 hour for heat treatment.
[0078] According to the standard SJ20966 2006, the performance of the prepared magnetic powder core was tested using an IWATSUB H analyzer (SY 8219). The test results are shown in Table 1.
[0079] Table 1 Performance of magnetic powder core of Example 1
[0080]
[0081] Example 2
[0082] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that iron, nickel, and aluminum are mixed in a mass percentage of 40:57:3.
[0083] Table 2 Performance of magnetic powder core of Example 2
[0084] 25℃ 50℃ 75℃ 100℃ Loss (50k 100mT) 423 289 110 167 Magnetic permeability 100k 1v 103 105 106 107 DC superposition 100k 1v 100oe 79.7% 79.0% 78.5% 78.4%
[0085] Example 3
[0086] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that in S202 the surface is subjected to a pressure of 10 kPa.
[0087] Table 3 Performance of magnetic powder core of Example 3
[0088] 25℃ 50℃ 75℃ 100℃ Loss (50k 100mT) 315 208 148 120 Magnetic permeability 100k 1v 114 118 119 119 DC superposition 100k 1v 100oe 80.1% 79.8% 78.4% 78.3%
[0089] Example 4
[0090] The present embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that S202 is as follows: the product of S201 is taken out and passed through a 200-mesh sieve, the material under the sieve is placed in an iron box, and an iron ingot is pressed on the product of S201 in the iron box so that its surface is subjected to a pressure of 5 kPa. On the basis of mechanical stress, the iron box is placed in a sintering furnace for annealing, the temperature is increased from room temperature to 750°C at a heating rate of 10°C / min, and the temperature is kept for 1 hour, and then the iron box is cooled to room temperature with the furnace, and the whole process is kept in a hydrogen atmosphere, and the furnace pressure is controlled at 0.2-0.3 MPa.
[0091] Table 4 Performance of magnetic powder core of Example 4
[0092] 25℃ 50℃ 75℃ 100℃ Loss (50k 100mT) 458 448 412 385 Magnetic permeability 100k 1v 119 119 120 120 DC superposition 100k 1v 100oe 74% 74.1% 74.1% 74%
[0093] Comparative Example 1
[0094] This comparative example provides a method for preparing a magnetic powder core, which is basically the same as Example 1, except that no aluminum is added in this comparative example, and iron and nickel are mixed in a mass percentage of 40:60.
[0095] Table 5 Performance of magnetic powder core of comparative example 1
[0096] 25℃ 50℃ 75℃ 100℃ Loss (50k 100mT) 359 378 449 621 Magnetic permeability 100k 1v 129 132 136 137 DC superposition 100k 1v 100oe 76% 75.6% 74.9% 73.2%
[0097] Comparative Example 2
[0098] This comparative example provides a method for preparing a magnetic powder core, which is basically the same as Example 1, except that there is no mechanical stress during the heat treatment of S2. S202 is: the product of S201 is taken out and passed through a 200-mesh sieve, the sieve-down material is placed in an iron box, and the iron box is placed in a sintering furnace for annealing, from room temperature to 340°C at a heating rate of 15°C / min, and kept warm for 0.5h, then to 750°C at a heating rate of 5°C / min, and kept warm for 1h, then to 620°C at a cooling rate of 1°C / min, and kept warm for more than 2h; then to 480°C at a cooling rate of 0.5°C / min, and then cooled to room temperature with the furnace, and kept in a hydrogen atmosphere throughout the process, and the furnace pressure was controlled at 0.2-0.3Mpa.
[0099] Table 6 Comparative Example 2 Magnetic Powder Core Performance
[0100] 25℃ 50℃ 75℃ 100℃ Loss (50k 100mT) 399 415 462 731 Magnetic permeability 100k 1v 119 119 120 120 DC superposition 100k 1v 100oe 77.2% 77.1% 77.1% 77%
[0101] From the comparison between Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the magnetic powder core prepared in the present invention has a negative temperature characteristic, and the loss gradually decreases as the temperature increases, and has an even lower loss at 100°C.
[0102] In combination with Examples 1 and 2, it can be seen that the present invention can control the magnetic loss performance at different temperatures by adjusting the ratio of iron, nickel and aluminum elements to meet different market application requirements.
[0103] Comparative Example 1 shows that the loss of the iron-nickel magnetic powder core without aluminum doping continues to deteriorate as the temperature increases.
[0104] Comparative Example 2 shows that when no mechanical stress is applied during the S2 treatment, the prepared iron-nickel magnetic powder core does not have negative temperature characteristics, and its loss is high and worsens with increasing temperature.
[0105] From the comparison between Examples 1 and 2 and Example 3, it can be seen that under the premise of applying mechanical stress in S2, a multi-stage heat treatment method is adopted, and the prepared magnetic powder core has negative temperature characteristics, while the loss of the magnetic powder core can be further reduced.
[0106] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a magnetic powder core, characterized in that: The following steps are involved: S1. preparing magnetic powder; The magnetic powder is an iron-nickel-aluminum alloy soft magnetic powder, wherein the mass percentage of iron is 37% to 42%, the mass percentage of nickel is 60% to 64%, and the mass percentage of aluminum is 2.5% to 3%; S2, heat treating the magnetic powder under pressure; S3, coating the product of S2; S4, pressing the product of S3 into a blank; S5. Heat-treating the blank to obtain a magnetic powder core.
2. The method for preparing a magnetic powder core according to claim 1, characterized in that: The S2 includes: S201, mixing magnetic powder with nano-mica powder and chromium trioxide; S202, heat treating the product of S201 under pressure; Preferably, the nano-mica powder is 0.1% to 0.2% of the mass of the magnetic powder; Preferably, the chromium trioxide is 0.05% to 0.1% of the mass of the magnetic powder; Preferably, the S201 comprises: firstly mixing the magnetic powder with the nano-mica powder to obtain a mixture, dissolving chromium trioxide in a first solvent to obtain a first solution, and then mixing the mixture with the first solution and drying; More preferably, the first solvent comprises one or more of acetone and water; More preferably, the first solvent accounts for 5% to 10% of the mass of the magnetic powder.
3. The method for preparing a magnetic powder core according to claim 1 or 2, characterized in that: The pressure in S2 is 5kpa~10kpa.
4. The method for preparing a magnetic powder core according to claim 1 or 2, characterized in that: Heat treatment in S2 includes: Heat up from room temperature to 340℃~380℃ at the first heating rate, and keep warm for 0.5~1h; continue to heat up to 740℃~750℃ at the second heating rate, and keep warm for 1~3h; cool down to 620℃~640℃ at the first cooling rate, and keep warm for more than 2h; cool down to 460~500℃ at the second cooling rate, and then cool down to room temperature with the furnace; Preferably, the first heating rate is 10-15°C / min; Preferably, the second heating rate is 5 to 8°C / min; Preferably, the first cooling rate is 1-2°C / min; Preferably, the first cooling rate is 0.5-1°C / min; Preferably, the hydrogen atmosphere is maintained throughout the heat treatment; Preferably, the furnace pressure of the heat treatment is controlled at 0.2-0.3 MPa.
5. The method for preparing a magnetic powder core according to claim 1 or 2, characterized in that: S1 includes: Iron, nickel and aluminum are mixed according to mass ratio, melted and atomized to obtain iron-nickel-aluminum alloy soft magnetic powder; Preferably, the melting temperature is 1500-1800°C and the melting time is 2-3h; Preferably, the melting is carried out under vacuum conditions; Preferably, the atomization is a high-pressure gas-water combined atomization method, and more preferably, the gas pressure of the high-pressure gas-water is 1 to 6 MPa; Preferably, S1 further comprises sieving to obtain magnetic powder with a particle size of 16 μm-34 μm.
6. The method for preparing a magnetic powder core according to claim 1 or 2, characterized in that S3 include: S301, mixing the product of S2 with a silane coupling agent; S302, mixing the product of S301 with silicone resin; Preferably, the silane coupling agent includes one or more of acrylic silane coupling agent, KH560 and KH570; more preferably, the silane coupling agent is A-189 silane coupling agent; Preferably, the silicone resin includes one or more of polydimethylsiloxane, methylphenyl silicone resin and methyl silicone resin; Preferably, the amount of the silane coupling agent is 0.5% to 0.6% of the mass of the magnetic powder; Preferably, the amount of silicone resin used is 0.8% to 1% of the mass of the magnetic powder.
7. The method for preparing a magnetic powder core according to claim 6, characterized in that: At least one of the following conditions is met: (1) S301 includes first dissolving the silane coupling agent in a second solvent to obtain a second solution, and then mixing the product of S2 with the second solution and drying; Preferably, the second solvent comprises one or more of acetone and water; Preferably, the second solvent is 5% to 10% of the mass of the magnetic powder; (2) S302 includes first mixing the silicone resin with a third solvent to obtain a third solution, and then mixing the product of S301 with the third solution and drying; Preferably, the third solvent comprises one or more of acetone and water; Preferably, the third solvent accounts for 5% to 10% of the mass of the magnetic powder.
8. The method for preparing a magnetic powder core according to claim 1 or 2, characterized in that: S4 comprises mixing the product of S3 with a release agent and then pressing and molding; Preferably, the release agent comprises zinc stearate and / or aluminum stearate; Preferably, the amount of the release agent is 0.3%-0.4% of the mass of the magnetic powder; Preferably, the pressure of the press molding is 1800-2000 MPa.
9. The method for preparing a magnetic powder core according to claim 1 or 2, characterized in that: S5 includes keeping the blank at 700-750° C. in a nitrogen atmosphere for 1-2 hours to obtain a magnetic powder core.
10. A magnetic powder core obtained according to the method according to any one of claims 1 to 9.